Brain Asymmetry in Evolution - Sawada, Kazuhiko (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In higher mammals, including primates and carnivores, the asymmetrical aspects of brain morphology and function have been shown to be species-related, sex-related, and subject to individual diversity, and are associated with cognition, emotion, language, preference of hand/paw use, and numerous other aspects. Disturbance of the brain lateralization is involved in human neurodevelopmental disorders with cognitive impairments, social deficits, and/or specific language impairments. Asymmetric development may be essential to the evolution of the brain in acquiring higher and/or more diverse functions. The purpose of this Special Issue on "Brain Asymmetry in Evolution" is to highlight morphological and functional lateralization of the brain in various species of mammals toward understanding the evolution of the brain.